2017
DOI: 10.3389/fphar.2017.00316
|View full text |Cite
|
Sign up to set email alerts
|

The Alkamide trans-Pellitorine Targets PPARγ via TRPV1 and TRPA1 to Reduce Lipid Accumulation in Developing 3T3-L1 Adipocytes

Abstract: Adipose tissue is an important endocrine organ in the human body. However, pathological overgrowth is associated with chronic illness. Regulation of adipogenesis and maturation of adipocytes via bioactive compounds in our daily diet has been in focus of research in the past years and showed promising results for agonists of the ion channels transient receptor potential channel (TRP) V1 and A1. Here, we investigated the anti-adipogenic potential and underlying mechanisms of the alkamide trans-pellitorine presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…Consistently with several reports showing that 3T3L1 fibroblasts endogenously express multiple TRP channel family members including TRPA1 and TRPV1 23,24 , we observed that 3T3L1 fibroblasts exhibit rises in [Ca 2+ ] i in response not only to APP-HBS exposure but also to either AITC or capsaicin, pharmacological activators of TRPA1 and TRPV1, respectively. Consequently, we confirmed all of these [Ca 2+ ] i responses induced by APP-HBS as well as by these chemical agonists to be significantly suppressed by siRNA-mediated knockdown of TRPA1 and/or TRPV1 (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Consistently with several reports showing that 3T3L1 fibroblasts endogenously express multiple TRP channel family members including TRPA1 and TRPV1 23,24 , we observed that 3T3L1 fibroblasts exhibit rises in [Ca 2+ ] i in response not only to APP-HBS exposure but also to either AITC or capsaicin, pharmacological activators of TRPA1 and TRPV1, respectively. Consequently, we confirmed all of these [Ca 2+ ] i responses induced by APP-HBS as well as by these chemical agonists to be significantly suppressed by siRNA-mediated knockdown of TRPA1 and/or TRPV1 (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Other Thermo-Sensitive TRP Channels In a pharmacological experiment, TRPA1 was shown expressed in the 3T3-L1 adipocyte cell line, 123) and indirect activation of TRPA1 by trans-pellitorine reduced lipid accumulation. However, functional expression of TRPA1 in adipocytes has not been well established.…”
Section: )mentioning
confidence: 99%
“… 26 , 38 However, CAL is also known as a potent agonist of TRPA1 channels, constituting nonselective thermosensitive cation channels, that have been identified in a variety of neuronal and nonneuronal cell types. 25 27 Multiple TRPA1-dependent actions for CAL have been reported over the last decades, such as immunomodulatory 39 and vasodilatory 40 actions as well as the secretion of hormones such as serotonin, 27 ghrelin, 12 and PYY. 41 Additionally, the role of TRP channels in the physiological processes of adipogenesis has grown as a topic of extensive research.…”
Section: Discussionmentioning
confidence: 99%